Proposed Ethical Work Behavior Model in Boundaries of Organizational Domain - Saeed, Behjati; Rana, Altounjy (International Journal of Engineering and Technology, 2018)
The organizational code of ethic plays a big role as linkage between the organizationâ€™s mission, values and principles with the standards of professional conduct. Due to this, the objective of this research is to identify the ethical work behavior and depict a baseline to predict the organizational code of ethic.Both inductive and deductive method of inquiry was adopted, starting with qualitative grounded theory as antecedent variables were bushed in linguistic form. The developed conceptual model, which was demonstrated by 28 items, measuring 6 constructs which tested the behavioral side of the ethical practices, in quantitative phase. The proposed â€œEthical work behavior modelâ€ was studied for generalizability by smart-PLS and test for [a] the loadings of studied items on their anticipated latent variables and also test [b] the proposed relationship among a set of dependent and independent constructs. Result of 168 distributed questioners in 30 different academic base organizations, indicates that both situational and individual leverage can explain and predict the ethical work behavior.Â